Effects of fertilizers on growth performance of Aquilaria malaccensis at Ayer Hitam Forest Reserve, Selangor - Amirudin, Natasya Amira (2018)
The planting of Aquilaria malaccensis has increased in Malaysia due to the value and usage of this plant. A. malaccensis also known as Karas, had lot of the benefits in term of medicine, religious usage and fragrant usage. This research was done to determine the effect of fertilizers on the growth performance of seedlings of Aquilaria malaccensis. This study was done at Ayer Hitam Forest Reserve, Selangor under the shade of Acacia mangium. In this study, NPK 15-15-15 was applied to the seedlings of one year old A. malaccensis at different rates of 50 g, 100 g, and 150 g, and the control was 0 g of fertilizer. The application of NPK 15-15-15 were done twice during this study. The growth parameters measured were the total height and diameters of the seedlings. Totalheight and diameter taken for six months, from October 2017 until March 2018. Results from this research showed that there were positive effects of growth performance of A. malaccensis from the application of NPK 15-15-15 towards the increment of total height and diameter. The results from both parameters showed that the higher rate of fertilizers which 150 g were more suitable for the growth of A. malaccensis. For recommendation, the study on application on different weight of fertilizer must be done to ensure either 150 g is the best rates of fertilizers or is there any rate of fertilizer are more suitable for growth of A. malaccensis.